2006
DOI: 10.1155/mi/2006/92642
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba Extract on Inflammatory Mediators (SOD, MDA, TNF‐α, NF‐κBp65, IL‐6) in TNBS‐Induced Colitis in Rats

Abstract: Inflammatory mediators play a criticial role in ulcerative colitis immune and inflammatory processes. The aim of the study was to investigate the effects of Ginkgo biloba extract on inflammatory mediators (SOD, MDA, TNF-α, NF-κBp65, IL-6) in TNBS-induced colitis in rats. Colitis in rats was induced by colonic administration with 2,4,6-trinitrobenzene sulfonic acid (TNBS, 150 mg/kg). EGB in doses of (50, 100, 200 mg/kg) was administered for 4 weeks to protect colitis. The results showed that EGB could signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 37 publications
6
85
0
1
Order By: Relevance
“…Some approaches for UC treatment include inhibition of ROS producing enzymes, direct scavenging of ROS or improvement of cellular antioxidant pools. As a possible mechanism herbal treatment could scavenge oxidative-free radicals, down-regulate some of the inflammatory mediators involved in the intestinal immune and inflammatory responses, including TNF-α, NF-κBp65 and IL-6 resulting in the improvement of UC (33). In our study, sterols, triterpenes, tanins, polyuronides, and saponines have been observed in the contents of the PC.…”
Section: Discussionsupporting
confidence: 48%
“…Some approaches for UC treatment include inhibition of ROS producing enzymes, direct scavenging of ROS or improvement of cellular antioxidant pools. As a possible mechanism herbal treatment could scavenge oxidative-free radicals, down-regulate some of the inflammatory mediators involved in the intestinal immune and inflammatory responses, including TNF-α, NF-κBp65 and IL-6 resulting in the improvement of UC (33). In our study, sterols, triterpenes, tanins, polyuronides, and saponines have been observed in the contents of the PC.…”
Section: Discussionsupporting
confidence: 48%
“…Oxidative stress and its consequent lipid peroxidation can aggravate free radical chain reactions, disrupt the integrity of intestinal mucosa barrier and activate pro-inflammatory responses. MDA, a marker of lipid peroxidative damage, and SOD, an important antioxidative enzyme, have been reported to increase and decrease in experimental colitis studies, respectively (20,21). Antioxidative and anti-inflammatory treatment improved these effects on the MDA level and SOD activity in experimental ulcerative colitis (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…ALA may be beneficial in preventing the development of MS by affecting the release of serum inflammatory cytokines-in other words, showing an anti-inflammatory effect [11,15,31] . In many previous studies, the beneficial effects of anti-inflammatory agents on MS have been shown [6,21,26,27,32] . In most of the experimental studies on myringosclerosis, histological and otomicroscopic evaluations were preferred.…”
Section: Discussionmentioning
confidence: 98%
“…After the revelation of the role of oxygen free radicals in the pathogenesis of MS, thanks especially to the study of Mattson et al [21] , many studies showed that this damage, caused by oxygen free radicals, could be successfully reduced or prevented by using antioxidant, free radical connective substances and anti-inflammatory agents that have been reported in the literature. Of these, ascorbic acid, vitamin E, selenium, L-carnitine, N-acetylcysteine , caffeic acid, ginkgo biloba, pomegranate, N-nitro L-arginine, steroids, and melatonin can be considered [6,17,[21][22][23][24][25][26][27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation